Technology and the demand for skill: an analysis of within and between firm differences - John M. Abowd; John Haltiwanger; Julia Lane; Kevin L. McKinney; Kristin Sandusky (Institute for the Study of Labor (IZA), 2007)
We estimate the effects of technology investments on the demand for skilled workers using longitudinally integrated employer-employee data from the U.S. Census Bureau's Longitudinal Employer-Household Dynamics Program infrastructure files spanning two Economic Censuses (1992 and 1997). We estimate the distribution of human capital and its observable and unobservable components within each business for each year from 1992 to 1997. We measure technology using variables from the Annual Survey of Manufactures and the Business Expenditures Survey (services, wholesale and retail trade), both administered during the 1992 Economic Census. Static and partial adjustment models are fit. There is a strong positive empirical relationship between advanced technology and skill in a cross-sectional analysis of businesses in both sectors. The more comprehensive measures of skill reveal that advanced technology interacts with each component of skill quite differently: firms that use advanced technology are more likely to use high-ability workers, but less likely to use high-experience workers. These results hold even when we control for unobservable heterogeneity by means of a selection correction and by using a partial adjustment specification.
urn:nbn:de:101:1-20080410108
Keywords: 330; Technologie; Investition; Innovation; Humankapital; Qualifikation; USA